Re(I) and Tc(I) Complexes for Targeting Nitric Oxide Synthase: Influence of the Chelator in the Affinity for the Enzyme. (7th May 2015) - Oliveira, Bruno L.; Morais, Maurício; Mendes, Filipa; Moreira, Irina S.; Cordeiro, Carlos; Fernandes, Pedro A.; Ramos, Maria J.; Alberto, Roger; Santos, Isabel; Correia, João D. G.
<x xml:space="preserve">Abstract</x> Aiming to design 99mTc complexes for probing nitric oxide synthase (NOS) by SPECT, we synthesized conjugates (L4–L6) comprising a NOS‐recognizing moiety connected to a diamino‐propionic acid (dap) chelating unit. The conjugates led to complexes of the type fac‐[M(CO)3(ĸ3‐L)] (M = Re/99mTc; Re4/Tc4: L = L4; Re5/Tc5: L = L5; Re6/Tc6: L = L6). Enzymatic studies showed that L4 and L5, but not L6, gave complexes (Re4 and Re5) that are less potent than the conjugates. To rationalize these results, we performed docking and molecular dynamics simulations. The high affinity of L4 and L5 is due to the strong interactions between the dap chelator and polar residues of the binding cavity. These interactions are hampered by metallation resulting in complexes with lower affinity. The higher potency of Re5 compared to Re4 was assigned to the increased bulkiness of Re5 and the presence of additional anchoring groups that better fit the active site and provide more extensive contacts. In turn, Re6 is too bulky and its organometallic tail is oriented toward the peripheral pocket of iNOS, leading to loss of contacts and a lower affinity. These results were compared with our previous results obtained with analogue complexes stabilized by a pyrazolyl‐diamine chelating unit.